Growth Performance and Digestibility of Red Sokoto Goat Fed Jatropha curcas Kernel Cake Treated with Pseudomonas aeruginosa (International Journal of Veterinary Medicine and Animal Science, 2025)
Good quality feed has been a major challenge in livestock production in the tropics, especially during the dry season, which is characterized by low-quality forages. Good nutrition is important because it is associated with improving the performance, health, reproduction and productivity of animals. This study aimed to evaluate the growth performance and digestibility of Red Sokoto goats fed Jatropha curcas kernel cake treated with Pseudomonas aeruginosa. Twenty Red Sokoto goats with average weight of 8.20±1.1kg were completely randomized into diets A (control: 0% Jatropha curcas kernel cake), B (10% Pseudomonas treated Jatropha curcas kernel cake), C (15% Pseudomonas treated Jatropha curcas kernel cake), and D (20% Pseudomonas a treated Jatropha curcas kernel cake). Jatropha curcas kernel cake was used as a replacement for groundnut cake over a 70-day experimental period. Data was analyzed as one-way ANOVA in SAS and means were separated with Duncan multiple range test at alpha of 5%. There was significant variation in the crude protein, ether extract and crude fiber of the experimental diets. A significant (p